Критерії та моделі оцінки ефективного управління державної служби - Левківська, Аліна Андріївна; Levkivska, Alina Andriyivna (Ірпінь, 2023)
Теоретико-прикладне визначення критеріїв та моделей оцінки ефективного управління державною службою в Україні

Theoretical and applied definition of criteria and models for evaluating effective management of civil service in Ukraine
Criteria and models for assessing the effective management of the state service
Keywords: державна служба; критерії; моделі; оцінка; ефективність; civil service; criteria; models; assessment; effectiveness